(untitled) (Research, Society and Development, 2022)
Introduction: Depression and anxiety disorder are psychic changes that affect the current and corresponding population for the fifth and sixth cause of disability in Brazil. Studies show that exercises, such as the Pilates method, that trains the body and the mind, can be suggested as an alternative treatment for treating disorders, syndromes and mental disorders. Objective: To analyze through an integrative literature review the effects of the Pilates method on mental health in patients with depression and anxiety disorder. Methods: This is an integrative review of the literature, of an exploratory and qualitative, non-systematic, in the Periódico Capes, Pubmed, Pedro and Scielo. Results: Eigth studies were analyzed, totaling 475 participants in which they pointed out that Médoto Pilates is beneficial in mental health and quality of life in practitioners who suffer from anxiety and depression disorders. Only 1 study did not identify differences between treatment with Pilates and conventional treatment. Conclusion: The Pilates method can become a great ally in the treatment of individuals with Anxiety Disorder and Depression.